Factors Influencing Institutional Delivery Among Reproductve-Age Women in Bagmati Province, Nepal - Devkota, Bijaya M.; Devkota, Govinda P. (Historical Journal, 2025)
Reproductive age on institutional delivery among the women of Bagmati Province in Nepal, descriptive and bivariate logistic regression analysis. The data present a strong relationship between maternal age and institutional delivery (p=0.01), with women aged 30–49 years being more likely to deliver in health facilities than women under 20 years (OR=14.73). Adolescent mothers, being younger, are more exposed to social and economic factors that limit their awareness and access to institutional delivery. In contrast, older women often have greater autonomy in decision-making processes. Education showed a significant association with institutional delivery in the bivariate analysis, but this effect diminished in the multivariate analysis, suggesting that wealth and residence mediated this relationship. Cultural and caste-based factors influence institutional delivery, particularly among the Janajati, Terai, and Brahmin/Chhetri communities. Residence plays a key role as 77.4 percent of institutional deliveries occurred in urban areas. The most significant determinant of institutional delivery was wealth, with women in the richest quintile being 25.26 times more likely to deliver in a health facility compared to those in the poorest quintile (p=0.00). These findings suggest that further research is needed, particularly longitudinal and qualitative studies, to better understand the socio-cultural factors that influence maternal health outcome.